2019
DOI: 10.3389/fchem.2019.00878
|View full text |Cite
|
Sign up to set email alerts
|

Free-Standing SnO2@rGO Anode via the Anti-solvent-assisted Precipitation for Superior Lithium Storage Performance

Abstract: Metal oxides have been attractive as high-capacity anode materials for lithium-ion batteries. However, oxide anodes encounter drastic volumetric changes during lithium ion storage through the conversion reaction and alloying/dealloying processes, leading to rapid capacity decay and poor cycling stability. Here, we report a free-standing SnO 2 @reduced graphene oxide (SnO 2 @rGO) composite anode, in which SnO 2 nanoparticles are tightly wrapped within wrinkled rGO sheets. The SnO 2 @rGO sheet is assembled in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…FESEM was conducted to characterize the surface morphology of the rGO and SnO 2 -rGO composite. As depicted in Figure 3 a, under 50 kX magnification, wrinkles made of stacks of single rGO layers can be found everywhere on the surface, which matches with amorphous rGO characteristics [ 36 ]. As vividly demonstrated in Figure 3 b, synthesized SnO 2 -rGO consists of highly crystalline and spherical constituents, which verify the existence of SnO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…FESEM was conducted to characterize the surface morphology of the rGO and SnO 2 -rGO composite. As depicted in Figure 3 a, under 50 kX magnification, wrinkles made of stacks of single rGO layers can be found everywhere on the surface, which matches with amorphous rGO characteristics [ 36 ]. As vividly demonstrated in Figure 3 b, synthesized SnO 2 -rGO consists of highly crystalline and spherical constituents, which verify the existence of SnO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Jiang et al [203] developed a SnO 2 /rGO nanocomposite, which showed an initial specific capacity of 1705 mAh g −1 and a capacity retention of 500 mAh•g −1 after 50 cycles at 250 mA g −1 . A free-standing SnO 2 @rGO composite anode, in which SnO 2 nanoparticles were tightly wrapped within wrinkled rGO sheets, was synthesized via an anti-solvent-assisted precipitation [204]. The SnO 2 @rGO anode showed significant enhanced lithium storage behavior; a high charge capacity above 700 mAh g −1 was achieved with 95.6% retention after 50 cycles at a current density of 0.5 A g −1 .…”
Section: Tin-based Oxide Compositesmentioning
confidence: 99%
“…In order to address those issues new electrode materials are explored, implying in case of the anode that the currently used graphite with its rather low theoretical capacity of 372 mAh g −1 has to be replaced. [ 1–4 ]…”
Section: Introductionmentioning
confidence: 99%
“…SnO 2 attracted lots of attention as a promising alternative featuring a high theoretical capacity of 1494 mAh g −1 and a low working potential. [ 1–3,5 ] Lithiation and delithiation of SnO 2 can be subdivided into two main steps. In a first step, SnO 2 undergoes a conversion reaction resulting in the formation of metallic Sn embedded into a Li 2 O matrix followed by alloying reactions between lithium and the previously formed Sn phase yielding Li x Sn (0 ≤ x ≤ 4.4).…”
Section: Introductionmentioning
confidence: 99%